11 Is pulmonary artery dilatation part of the athletic adaptation to exercise?. (6th June 2022) - Chatrath, Nikhil; Quazi, Kashif; Fyyaz, Saad; Bhatia, Raghav; MacLachlan, Hamish; Rowntree, Christopher; Marwaha, Sarandeep; Esteban, Maria Teresa Tome; Sharma, Sanjay; Papadakis, Michael
Abstract : Introduction: The 'Athlete's Heart' is a well-established term used to describe the spectrum of structural and electrical cardiac adaptations to intensive exercise. Several studies have demonstrated the development of ventricular dilatation and hypertrophy in athletic individuals and cardiac magnetic resonance imaging (CMR) is well suited to assess these changes. However, there is a paucity of studies looking at pulmonary artery (PA) dimensions in athletic individuals. One could hypothesize that increased stroke volumes and pulmonary flow may cause dilatation of the PA. The aim of this study is to ascertain whether PA dilatation is part of the cardio-pulmonary adaptation to intensive exercise and establish normal parameters of PAs in athletes. Methods: The CMRs of male athletes performed at a single-centre between January 2017 and October 2021 were reviewed. Those with any evidence of a structural abnormality or cardiomyopathy were excluded. The volumes of all cardiac chambers were recorded, indexed to body surface area (BSA). The PA was measured in the transaxial stack at the level of the bifurcation of the main PA. This was repeated for a control group of sedentary individuals with otherwise structurally normal hearts. Sporting discipline of the athletes and sedentary status of the controls was confirmed by retrospective review of the patents' clinical records. Differences between the two groups were compared, with statistical significance for P-values set at <0.05. Results: The CMRs of 169 male athletes were compared with 95 male sedentary controls. There was no difference in the mean ages of the groups (athletes 33±11 years (range 17–59) versus controls 30±13 years (range 17–60); p=0.10)The main indications for CMR in the athletic cohort included cardiac symptoms 25% (n = 44), ECG abnormalities 24% (n = 41) and screening due to a family history of cardiac disease 22% (n=37). The majority of athletes engaged in endurance sport (60%; n=101) and football (18%, n=30).The differences between the groups is shown in table 1. The volumes of all cardiac chambers, were significantly larger in the athletes. LV ejection fraction (LVEF) was significantly lower in athletes. The mean pulmonary artery in athletes was significantly larger than in sedentary controls (athletes 25.1(±3.7)mm vs controls 22.4(± 3.0)mm). The distribution of PA diameters is shown in figure 1. There was no significant correlation between PA diameter and either RV end-diastolic volume (r=0.10) or RV stroke volume (r=0.04). Incidentally, a significantly higher proportion of athletes had fibrosis at the RV insertion point. Conclusion: Male athletes have a significantly larger PA than sedentary controls with 22% athletes having a PA≥27 mm compared to just 7% of controls. This suggests that PA dilatation may be part of the cardiopulmonary adaptation to exercise.These findings need corroboration in larger-scale, prospective studies, including pulmonary pressures and a wider array of sporting disciplines. The long-term implications of pulmonary artery dilatation in athletes is unknown but it may be used as an additional parameter to indicate athletic adaptation. Conflict of Interest: Nil